DEVELOPMENT OF SUGGESTOPEDIA MODEL BASED ON STRENGTHENING OF CHARACTER EDUCATION FOR INCREASE THE ABILITY TO WRITING POETRY IN ELEMENTARY SCHOOL (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This research was motivated by empirical facts about the increasing lack of interest in reading literature for elementary school students. This implication have an impact on learning Indonesian language, one of which is the ability to write poetry in elementary school. This study aims to test the effectiveness of suggestopedia model based on the strengthening of character education in elementary school students. Through the lesson plan by inserting five main values of character, such as religious, nationalist, independent, cooperation, and integrity. In order to achieve the goal of researchers conducted a study consist of three stages: (1) Develop a model, (2) Carry out field trials with the design of pre-test-posttest control group experimental design involving 70 students in two class one of elementary school in Bogor of including 35 experimental groups and a control group of 35 students and (3) Prepare the final model by revising the end of model has been tested. The analysis shows that suggestopedia model based on the strengthening of character education was effective for improving the ability to write poetry of elementary school. It can be seen from the reality of the condition after treatment in the control class or experimental class are equally increased, but the condition is more increased in the experimental class. suggestopedia model based on the strengthening of character education as one of models can be used in developing ability to write poetry using criteria of assessment, such as theme and meaning, diction, imajination, and message.